KETERLIBATAN KELUARGA DALAM MANAJEMEN, KEPEMILIKAN KELUARGA, DAN KINERJA PERUSAHAAN: BUKTI EMPIRIS DARI BURSA EFEK INDONESIA - perminas pangeran (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2018)
The objective of this study is to examine the effect of family involvement in firm’s management and family ownership on financial performance. The sample of this study are 8 family firms that listed in Indonesian stock exchange during 2012-2015. This research used multiple regression technique. The results of this study indicated that family ownership had a negative effect on campanies financial performance, while the family involvement in the firm’s management had no significant effect on campanies financial performance.